PENGARUH PERSONAL SELLING TERHADAP SIKAP KONSUMEN MEMILIH PRODUK ASURANSI (KASUS PT. ASURANSI JIWASRAYA (PERSERO) CABANG PEKANBARU) - Sitompul, Hanna; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
PT. Asuransi Jiwasraya (Persero) Pekanbaru Branch is the only one branch of PT. Asuransi Jiwasraya in Pekanbaru is located at Jl. Jenderal Sudirman 341 Pekanbaru. PT. Asuransi Jiwasraya (Persero) Pekanbaru Branch doing personal selling is one of promotion mix. The implementation of personal selling expected to change the mind of consumen of buying the product of insurance.The sample that as many as 97 respondents from population and taken by slovin’s formula. The data analysis of the research is statistical analysis whom supported by SPSS versi 20. The results of coefficient of determination was 0,949. This means that personal selling affects customer behavior of 94,9%.Key words: personal selling, customer behaviour, PT. Asuransi Jiwasraya (Persero) Pekanbaru Branch